Study of Synthesis of Ethyl-2-(4-Allyl-2-Methoxyphenoxy)Acetate in Polar Aprotic Solvents - Fadlan, Arif; Masitoh, Heni; Niadisti, Bella Ratih Apsari; Khusnayaini, Intan Ali; Agustin, Lela; Roshuna, Jean Fitriani (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
Eugenol, a phenol-derived aromatic allylbenzene compound, exhibits a wide spectrum of biological activities (antifungal, antibacterial, antioxidant, analgesic, and antiseptic) and is an active ingredient in various hygiene products. It contains three reactive groups (hydroxy, allyl, and methoxy) and undergoes several reactions, including alkylation. The modification of the hydroxyl group of eugenol through alkylation has been performed using different alkylating agents. Alkylation has been carried out in various solvents (benzene, acetonitrile, methanol, and water) and at diverse temperatures. Hence, the investigation of this alkylation reaction on eugenol remains challenging. Correspondingly, the present study investigated the alkylation of eugenol by ethyl chloroacetate in polar aprotic solvents (N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile, and tetrahydrofuran) at temperatures ranging from 0°C to room temperature. The product, ethyl 2-(4-allyl-2-methoxyphenoxy)acetate (3), was obtained in yields of 91%, 51%, and 47% using DMF, DMSO, and CH3CN, respectively. The product's structure was confirmed by NMR, IR spectroscopy, and HRESIMS analysis.